International handbook of play therapy advances in assessment, theory, research, and practice - Schaefer, Charles E.; McCormick, Judy; Ohnogi, Akiko J. (IG library, 2010)
Addresses a variety of topics relevant to the field of play therapy. This book provides play therapists with information that they can put into use in their clinical work with children and adolescents. It focuses on developments in assessment, theory, research, and practice that have universal appeal.